An interactive method for the analysis of the simulation of vehicle–bridge coupling vibration using ANSYS and SIMPACK. (March 2018) - Li, Yongle; Xu, Xinyu; Zhou, Yu; Cai, CS; Qin, Jingxi
Vehicle–bridge coupling vibration is a complicated interaction process, which includes multibody dynamics of vehicles, structural dynamics of bridges, and wheel–rail contact relationships. A single software is not adequate for the coupling analysis. Therefore, to efficiently conduct the vehicle–bridge coupling vibration analysis, an interactive method that integrates the commercial finite element software ANSYS and the multibody system software SIMPACK was presented in this study. The method takes advantage of the high modeling efficiency of ANSYS and the powerful wheel–rail analysis ability of SIMPACK. Two interactive methods, the dummy body coupling method and the equivalent flexible track method, were presented, and the merits and demerits of the two methods were compared in detail. Finally, the equivalent flexible track method was adopted for the analysis. The interactive method that was presented was confirmed to be feasible by the continuous bridge example, and the simulation for the long-span bridge was discussed further. It is shown that the interactive method has high computational efficiency and good convergence rate for various bridges, and the vehicle–bridge coupling vibration analysis can be conducted well and followed conveniently by other researchers.